Iranian feminist activits and critical media literacy - Kobra, Mohammadpour Kachalmi; Lee, Yok Fee (2018)
Considering the exponential growth of technology and media in Iranian society as well as the significant role of media culture in reproducing, reinforcing, and legitimizing dominant ideologies such as sexism, the central question posed by this paper is how Iranian feminist activists critically analyze media messages. Further, this paper explores the extent to which this analysis fits the critical media literacy framework. Using a critical media literacy framework underpinned by feminist standpoint theory, this paper presents results from qualitative interviews with 15 Iranian feminist activists. We find that Iranian feminist activists focus more on politics of representation and critique of gender ideology in the critical analysis of media products. Thus, critical analysis of media by Iranian feminist activists better fits the definition of critical media literacy than its core concepts. The findings also demonstrate that a transformative dimension of critical media literacy is ignored by the feminist activists despite using media in the struggle against dominant gender ideology.